Attention as a Process of Selection, Perception as a Process of Representation, and Phenomenal Experience as the Resulting Process of Perception Being Modulated by a Dedicated Consciousness Mechanism - Bachmann, Talis (Frontiers Research Foundation, 2011)
Equivalence of attention and consciousness is disputed and necessity of attentional effects for conscious experience has become questioned. However, the conceptual landscape and interpretations of empirical evidence as related to this issue have remained controversial. Here I present some conceptual distinctions and research strategies potentially useful for moving forward when tackling this issue. Specifically, it is argued that we should carefully differentiate between pre-conscious processes and the processes resulting in phenomenal experience, move the emphasis from studying the effects of attention on the modality-specific and feature-specific perception to studying attentional effects on panmodal universal attributes of whatever conscious experience may be the case, and acknowledge that there is a specialized mechanism for leading to conscious experience of the pre-consciously represented contents autonomous from the mechanisms of perception, attention, memory, and cognitive control.